A Note on Filopaludina martensi martensi (Frauenfeld, 1865) Artificial Breeding Conditions - Kroum Kroumov Hristov (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchLong-term maintenance of Filopaludina martensi martensi in artificial conditions (local tap-water and food).Observation of breeding behaviour of F. m. martensi.Observation of birth and development of the juveniles. AbstractFilopaludina martensi martensi Frauenfeld 1865 is an aquatic Viviparidae gastropod found in Thailand, and throughout Southeast Asia. It is popular in the local cousin, a vector of food-borne trematode infections, and used as a bio-indicator of heavy metal contamination, bio-control agent against Bithynia siamensis Lea 1856, and a way to reduce the total organic matter content from faeces and feed residue during Clarias sp. catfish and Nile tilapia aquaculture. The study aims to establish a protocol for breeding F. m. martensi snails in artificial conditions. The snails were maintained in laboratory conditions. The animals gave birth (3 - 4 juveniles) every month. Inflatable, for several hours after the birth, transparent lightly bluish (5 - 6 mm in diameter) spheres are released in which the fully mature juvenile moves, and leaves several hours later after the sphere breaks. All juveniles studied here die after 2 - 3 months failing to grow into a reproductive adults. F. m. martensi is an attractive animal that regardless of the current difficulties to maintain and grow its juveniles may be popularised in the ornamental fish trade, and a possible laboratory model animal.